The Mediating Effect Of Jit On The Relationship Between SCOR Model On Supply Chain Performance - Kamarudin, Nurhayati (2020)
The SCOR Model is one of the most applied reference models to support the description of supply chains and understanding the relationship between supply chain operation reference and supply chain performance. The Supply Chain Operations Reference (SCOR) model owes a standard thought to perceive an activity of the Supply Chain Council that provides a framework for characterizing supply chain management practices and processes with the result in better performance. This study examines potentials for future extensions of the model. The survey has been distributed to 270 companies in Malaysia manufacturing industry for extension potentials population. By an exhaustive analysis of 158 samples were returns to be evaluated for this study. This study investigates the level of SCOR Model practices in Supply Chain performance and investigates the relationship between supply chain operation reference (SCOR) Model effect by mediating of Just-In-Time (JIT) and supply chain performance in Malaysia manufacturing industry based on the five decision areas provided in SCOR Model Version 10.0 (PLAN, SOURCE, MAKE, DELIVER, RETURN) and five key supply chain performance derived from supply chain business management experts. The questionnaire tool by Supply Chain Council is used to analyse requirements on modelling tools to support the application of a respective extended SCOR Model. A concept of a tool support which accomplishes most of the requirements is described and realised as a prototype which is introduced in this thesis. The results show that planning processes are important in all SCOR supply chain planning decision areas. Collaboration was found to be most important in the Plan, Source and Make planning decision areas, while teaming was most important in supporting the Plan and Source planning decision areas. Process measures, process credibility and process integration were found to be most critical in supporting the deliver planning on the decision area. Using these results, the study discusses the implications of the ﬁndings and suggests several venues for future research.